Study on the effects of nozzle distance to surface roughness of workpiece under minimum quantity lubricant (MQL) milling process - Firdaus Shazriq, Mohd Fadzil; Nur Izzati Khoirunnisa, Ismail; Nurrina, Rosli (Universiti Malaysia Pahang, 2018)
Application of cutting oil during machining process has been the most important contributor for the development of manufacturing sectors. There are many types of machining technologies developed with cutting oil supply system such as minimum quantity lubricant (MQL). With very little supply of lubricant, it can lengthen the cutting tool life and surface roughness of workpiece. Although the low consumption of lubricant is favourable, study on the performance of MQL machining process must be strengthened enough since the high penetration ability of very little amount of lubricant oil is important. Many researches have been carried out since decades ago to study the MQL performance. However, investigation on the effects on nozzle position have not been treated in much detail. Here, this paper is aimed to investigate the effects of nozzle distance to surface roughness of workpiece under MQL milling process. Experimental approach was done mainly under different nozzle distance varied in horizontal direction from the cutting tool. Other than that, the effects of feed rate and spindle speed to the surface roughness were also investigated. As a result, surface roughness increases with increasing feed rate. At lower operation of spindle speed, surface roughness rapidly increases with increasing feed rate compared to higher operated spindle speed. Operation under high feed rate leads to a decreasing surface roughness with increasing spindle speed. Milling under high feed rate for all conditions of nozzle distance can still give a great surface roughness for a workpiece, only if the spindle speed is increased. Surface roughness decreases with increasing distance of nozzle to workpiece in horizontal direction.